Feminism and the ethics of care - D. Knapp van Bogaert; G.A. Ogunbanjo (South African Family Practice)
In a world where the physician-patient relationship is dominated by “male” values of autonomy and rights, space must be given to the no less important “feminine” values of care and connectivity. Both are necessary and complementary.